Pengaruh Desa Wisata terhadap Perekonomian Masyarakat Lokal dengan Syariah Marketing Tactic Sebagai Variabel Intervining - Nurul Inayati Rohmatin; Siti Kalimah (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2020)
The tourism village is a rural area that has several special characteristics to become a tourist destination. in this region, the population still has relatively original traditions and culture. In addition, several supporting factors such as special food, agricultural systems, and social systems also color a tourist village area. This study aims to determine the effect of rural tourism on the economy of the community through sharia marketing tactics, in the tourism village of Semarang regency. This study uses a quantitative approach, using SPPS version 16 to test validity and reliability, the classic assumption test, the determinant coefficient test, the hypothesis test, and the path analysis test. The technique used in collecting data in this study is by observation and questionnaire. The results showed that there was a significant influence between the tourism villages through sharia marketing tactic on the economy of the local community. This is evidenced by the results of the Fcount test of 23,930 with a significant value of less than 0.05 with the regression coefficient having a positive value of 0,000. The indirect effect caused by 0.591, so the contribution of tourism villages and the economy of the local community simultaneously which directly affect sharia marketing tactic of Rsquare = 0.246 or the remaining 24.6% of 0.754 = 75.4% influenced by other factors that cannot be explained in research.